A sign of affection. 10 - Dashiell, Christine, 1984-; Vanstiphout, Carl; Blakeslee, Lys, 1985- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2024)
"Since they started going out, the handsome and confident Itsuomi has been nothing but kind and caring toward Yuki, his deaf classmate and now girlfriend. The two have knocked down one challenge after another: staying in touch while Itsuomi is overseas, dealing with friends with unrequited crushes, and finally securing permission from Yuki's parents to move in together. Now the big day is finally here, and they've just finished bringing the last box into their new home. But now that all that work is done, the most nerve-wracking part begins: everyday life!"--